Pengetahuan Berhubungan Dengan Peran Perawat Dalam Pelayanan Perawatan Menjelang Ajal (Paliatif) - Mevi Lilipory (Lembaga Penerbitan Fakultas Kesehatan Universitas Kristen Indonesia Maluku, 2022)
Palliative care is care given to patients with chronic and terminal illness that aims to improve the patients and families’ quality of life. This study aims to determine the relationship of knowledge with the role of nurses in dying care services in the Inter Inpatient Room and ICU Room of RSUD Dr. M. Haullusy Ambon. The research design used was descriptive correlational with cross sectional The number of samples in this study were 45 respondents. The result was analyzed using the chi square test which found that the correlation between two variables of this research is significance at level 0.01. This means that there is a relationship between knowledge and the role of nurses in the care services near death (palliative) in the Internal Inpatient Room and ICU Room Dr. M. Haullussy Ambon Hospital. Based on the result of the study, the conclusion is that the knowledge and the role of care has a significance relationship with a value of p <0.001 (p <0.01). The suggestion of this research for the all nurses is to enhance their knowledge and role by attending seminars or training activities in order to improve performance and also the quality of service.Keywords: Knowledge, Role of Nurses, Palliative Care